2017
DOI: 10.1556/2006.6.2017.073
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Internet use disorder and attention deficit hyperactivity disorder: Two adult case–control studies

Abstract: ObjectivesThere is good scientific evidence that attention deficit hyperactivity disorder (ADHD) is both a predictor and a comorbidity of addictive disorders in adulthood. These associations not only focus on substance-related addictions but also on behavioral addictions like gambling disorder and Internet use disorder (IUD). For IUD, systematic reviews have identified ADHD as one of the most prevalent comorbidities besides depressive and anxiety disorders. Yet, there is a need to further understand the connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…suggest that as levels of social anxiety increase and people spend less time in real‐life relationships and more time on the Internet, their risk of developing PIU becomes greater . Many studies have shown a relation between PIU and ADHD . Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance‐related dependence and gambling dependence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggest that as levels of social anxiety increase and people spend less time in real‐life relationships and more time on the Internet, their risk of developing PIU becomes greater . Many studies have shown a relation between PIU and ADHD . Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance‐related dependence and gambling dependence .…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Regardless of PIU, many reports indicate that ADHD is related to behavior dependence, such as substance-related dependence and gambling dependence. [56][57][58] Behavioral features of ADHD symptoms are said to be lack of selfcontrol, 31,55 and it is fair to consider that such symptoms can lead to PIU. However, based on these observational studies, it is hard to understand the causal relationship of PIU and the aforementioned psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The impairments associated with ADHD across the lifespan are impressive. ADHD is associated with learning difficulties, school dropout, underachievement at work [126], frequent job changes [127], chronic fatigue [128], financial problems, gambling and internet use [129, 130], home and traffic accidents leading to increased mortality rates [131133], relationship difficulties and intimate partner violence [134, 135], early onset of addiction [136], teenage pregnancies and sexual transmitted diseases [137, 138], a two-fold increased smoking rate [139], an increased number of suicide attempts and self-harm in adolescents [140, 141], and increased criminality [142, 143]. Moreover, physical disorders and ailments may become chronic due to forgetfulness, health problems induced by a negative lifestyle, poor eating and sleeping habits, and lack of health care follow-up [144147].…”
Section: Icd and Dsm Criteria For Adhdmentioning
confidence: 99%
“…Problematic Internet use (PIU) has been found to resemble substance-related and other addictive disorders on a behavioral (Bielefeld et al, 2017;Grant, Potenza, Weinstein, & Gorelick, 2010) and neurobiological level (Dong, Huang, & Du, 2011). In addition, the evidence is suggestive of a comorbidity between them (Sussman, Lisha, & Griffiths, 2011).…”
Section: Introductionmentioning
confidence: 99%